Mycorrhizal fungi reduce nutrient loss from model grassland ecosystems - van der Heijden, Marcel G A (Ecology (Durham), 2010)
Nutrient loss from ecosystems is among the top environmental threats to ecosystems worldwide, leading to reduced plant productivity in nutrient-poor ecosystems and eutrophication of surface water near nutrient-rich ecosystems. Hence, it is of pivotal importance to understand which factors influence nutrient loss. Here it is demonstrated that arbuscular mycorrhizal (AM) fungi, widespread soil fungi that form mutualistic relationships with the majority of land plants, reduce nutrient loss from grassland microcosms during rain-induced leaching events. Grassland microcosms with AM fungi lost 60% less phosphorus and 7.5% less ammonium compared to control microcosms without AM fungi. Similar results were obtained for microcosms planted with each of three different grass species. In contrast, nitrate leaching was not affected by AM fungi but depended on the amount of nutrients supplied to the microcosms. Moreover, fertilization of the microcosms reduced the abundance of AM fungi and their ability to reduce phosphorus leaching losses. Extrapolation of these results suggests that the disruption of the mycorrhizal symbiosis is one of the reasons for enhanced phosphorus loss from fertilized ecosystems. The microcosms contained a sandy soil, a soil type vulnerable to leaching losses. The reduction of phosphorus leaching by AM fungi may, therefore, represent an upper limit. Advantages and limitations of the experimental setup for assessing the impact of AM fungi on nutrient cycling are discussed. The results indicate that AM fungi contribute to ecosystem sustainability by promoting a closed phosphorus cycle and reducing phosphorus leaching losses.